The effects of 8-week complex training on lower-limb strength and power of Chinese elite female modern pentathlon athletes - Qiao, Zining; Guo, Zhenxiang; Li, Bin; Liu, Meng; Miao, Guozhen; Zhou, Limingfei; Bao, Dapeng; Zhou, Junhong (Frontiers in Psychology, 2022)
Objectives: To examine the effects of complex training (CT) on lower limb strength and power of elite female modern pentathlon athletes. Methods: Ten female participants (age: 23.55±2.22 years, weight: 60.59±3.87 kg, height: 169.44±4.57 cm, and training experience: 6.90±2.08 years) of the national modern pentathlon team completed 8 weeks of resistance training (RT) as followed by 8 weeks of CT, with two weeks of break. Then the participants conducted 8 weeks of CT, which included RT combined with plyometric training (e.g., drop jump and continuous jump). All stages of training were designed by the linear strength training period theories, requiring participants to train twice for the first four weeks and three times for the second four weeks. The one-repetition maximum (1RM) of squat, isometric mid-thigh pull (IMTP), counter-movement jump (CMJ), squat jump (SJ), pre-stretch augmentation percentage (PSAP), and reaction strength index (RSI) were assessed before and after both RT and CT training. Results: The 1RM of squat was significantly improved (p < 0.001) after RT as compared to pre-RT. No significant improvement in IMTP (p = 0.055), CMJ (p = 0.194), SJ (p = 0.692), PSAP (p = 0.087), and RSI (p = 0.238) was not observed. After CT, 1RM of squat (p < 0.001), IMTP (p < 0.035), CMJ (p < 0.001), SJ (p < 0.008), RSI (p < 0.006) were significant improved as compared to pre-RT, post-RT and pre-CT, while significant improvements in PSAP were observed as compared to pre-RT (p = 0.003) and pre-CT (p = 0.027), but not to post-RT (p = 0.156). Conclusions: This pilot study showed the promise of CT to improve lower limb strength and power in elite female modern pentathlon athletes. The findings are worthwhile to be confirmed in future studies with larger sample size and randomized design.